Lesion probability mapping in MS patients using a regression network on MR fingerprinting - Hermann, Ingo; Golla, Alena-Kathrin; Martínez-Heras, Eloy; Schmidt, Ralf; Solana, Elisabeth; Llufriu, Sara; Gass, Achim; Schad, Lothar R.; Zöllner, Frank G. (BMC medical imaging, 2021)
To develop a regression neural network for the reconstruction of lesion probability maps on Magnetic Resonance Fingerprinting using echo-planar imaging (MRF-EPI) in addition to T1, T2∗, NAWM, and GM- probability maps.